Tools for Comprehensive Assessment of Fluid-Mediated and Solid-State Alteration of Carbonates Used to Reconstruct Ancient Elevation and Environments - Ingalls, Miquela; Snell, Kathryn E. (Frontiers in Earth Science, 2021)
Carbonates are ubiquitous in the rock record and provide a broad array of stable isotope-based paleoclimatic proxies (i.e., δ18O, δ13C, ∆17O, ∆47, ∆48) that provide information on stratigraphy, carbon cycling, temperature, hydrology, and the altitude of ancient land surfaces. Thus, carbonates are an essential archive of environmental and topographic histories of continental terranes. However, carbonate minerals are highly susceptible to post-depositional alteration of primary isotopic values via fluid-mediated and solid-state reactions. We propose a hierarchical suite of techniques to comprehensively assess alteration in carbonates, from essential and readily accessible tools to novel, high-resolution techniques. This framework provides a means of identifying preserved textures in differentially altered samples that contain high-value environmental information. To illustrate this progressive approach, we present a case study of Tethyan nearshore carbonates from the Paleocene Tso Jianding Group (Tibet). We demonstrate the utility of each technique in identifying chemical and crystallographic indicators of post-depositional alteration at progressively finer spatial scales. For example, secondary ionization mass spectrometry (SIMS) oxygen isotope maps of micrite and bioclasts reveal significant isotopic heterogeneity due to grain-scale water-rock exchange in textures that were labeled “primary” by optical inspection at coarser spatial resolution. Optical and cathodoluminescence microscopy should be the minimum required assessment of carbonate samples used in stable isotope analyses, but supplemented when necessary by SIMS, PIC mapping, and other yet untapped technologies that may allow distinction of primary and altered fabrics at finer spatial resolutions.